On-line Diagnosing on Trayed Column of Etylene Plant Using Gamma Ray Scanning - S. Sugiharto (Atom Indonesia, 2012)
Nuclear based technology called gamma scanning technique found its application for troubleshooting and diagnosing industrial process performance. The success of application of the gamma scanning technique is attributed to its unique ability in providing information which is cannot be obtained by any other techniques. One of the most prominent advantages of the gamma scanning technique was demonstrated by implementing this technology for scanning caustic/water wash tower DA 202 which was running in normal condition of operation. The DA 202 tower is trayed column having diameter of 4.2 m and height of 40 m. The scanning work has been performed using 70 mCi 60Co isotope as gamma emitter and scintillation detector as radiation counter to investigate condition of ten trays, starting from tray # 13 at elevation of 35050 mm to tray # 4 at elevation of 26950 mm above ground level. Scan data show that all trays were in their position. Tray # 4 to tray #10 were functioned properly and carried approximately the same amount of liquid. Light flooding on tray # 11 and heavy flooding on tray # 12 were identified. Partial flooding was identified on tray # 13. Further examination at the time of shutdown it was found that the liquid flooding on tray # 12 was caused by presence of a bucket covered with solidified mud. Received: 05 December 2011; Revised: 17 December 2012; Accepted: 18 December 2012